2018
DOI: 10.1002/bies.201700208
|View full text |Cite
|
Sign up to set email alerts
|

The Eukaryotic CMG Helicase at the Replication Fork: Emerging Architecture Reveals an Unexpected Mechanism

Abstract: The eukaryotic helicase is an 11-subunit machine containing an Mcm2-7 motor ring that encircles DNA, Cdc45 and the GINS tetramer, referred to as CMG (Cdc45, Mcm2-7, GINS). CMG is "built" on DNA at origins in two steps. First, two Mcm2-7 rings are assembled around duplex DNA at origins in G1 phase, forming the Mcm2-7 "double hexamer." In a second step, in S phase Cdc45 and GINS are assembled onto each Mcm2-7 ring, hence producing two CMGs that ultimately form two replication forks that travel in opposite direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 99 publications
(247 reference statements)
2
57
0
Order By: Relevance
“…The key mechanism for establishing a stable association of replisomes with the replication forks is the maintenance of DNA in the hole of the ring‐shaped structure of replicative helicases. Replicative helicases, including gp4 in bacteriophage T7 , DnaB in Escherichia coli , MCM homo‐hexamer–Cdc45/RecJ‐like protein–GINS complex in archaea , and Cdc45, Mcm2–7 hexamer and GINS complex (CMG complex) in eukaryotes , have a ring‐like shape and are considered to hold unwound ssDNA in the hole of the ring . The helicases bound stably to DNA associate with DNA polymerase, which also binds to unwound ssDNA for DNA synthesis and interacts with a clamp complex, the β clamp in E. coli , or PCNA in eukaryotes.…”
Section: Stable Association Between the Replication Fork And Replisomementioning
confidence: 99%
“…The key mechanism for establishing a stable association of replisomes with the replication forks is the maintenance of DNA in the hole of the ring‐shaped structure of replicative helicases. Replicative helicases, including gp4 in bacteriophage T7 , DnaB in Escherichia coli , MCM homo‐hexamer–Cdc45/RecJ‐like protein–GINS complex in archaea , and Cdc45, Mcm2–7 hexamer and GINS complex (CMG complex) in eukaryotes , have a ring‐like shape and are considered to hold unwound ssDNA in the hole of the ring . The helicases bound stably to DNA associate with DNA polymerase, which also binds to unwound ssDNA for DNA synthesis and interacts with a clamp complex, the β clamp in E. coli , or PCNA in eukaryotes.…”
Section: Stable Association Between the Replication Fork And Replisomementioning
confidence: 99%
“…The C-tier contains the motors with ATP sites located at subunit interfaces (Davey et al, 2003;Lyubimov et al, 2011). The ATP binding site of bacterial helicases is based on the RecA fold, while eukaryotic helicase ATP sites are based on the AAA+ fold (Erzberger and Berger, 2006;Li and O'Donnell, 2018;Lyubimov et al, 2011;O'Donnell and Li, 2018). While bacterial replicative helicases travel 5'-3' with the C-tier motors leading the way, eukaryotic helicases track 3'-5' on DNA with the N-face in front, pushed by motors in the C-tier (Enemark and Joshua-Tor, 2008;Li and O'Donnell, 2018;O'Donnell and Li, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ATP binding site of bacterial helicases is based on the RecA fold, while eukaryotic helicase ATP sites are based on the AAA+ fold (Erzberger and Berger, 2006;Li and O'Donnell, 2018;Lyubimov et al, 2011;O'Donnell and Li, 2018). While bacterial replicative helicases travel 5'-3' with the C-tier motors leading the way, eukaryotic helicases track 3'-5' on DNA with the N-face in front, pushed by motors in the C-tier (Enemark and Joshua-Tor, 2008;Li and O'Donnell, 2018;O'Donnell and Li, 2018). The way in which helicases engage ssDNA in the motor domains has been documented for several different hexameric replicative helicases and involve binding to loops in the ATPase domains (Abid Ali et al, 2017;Enemark and Joshua-Tor, 2006;Gao et al, 2019;Itsathitphaisarn et al, 2012;Li and O'Donnell, 2018;Meagher et al, 2019;O'Donnell and Li, 2018;Skordalakes and Berger, 2006;Thomsen and Berger, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar assay, we showed that the N-terminal end of MCM in Drosophila CMG interacts with parental DNA at the fork in an analogous manner (Eickhoff et al, 2019) suggesting that the mode of helicase engagement with DNA is conserved between Drosophila and yeast. A possible exit route for the displaced lagging-strand template was proposed to be formed by cavities between MCM ZF protrusions (Eickhoff et al, 2019, Li andO'Donnell, 2018). If the displaced strand exits through a narrow opening between MCM ZF domains during unwinding, CMG is expected to pause when colliding with a bulky obstacle on this strand.…”
Section: Cmg Bypasses a Protein Directly Crosslinked To The Excludedmentioning
confidence: 99%